1993
DOI: 10.1116/1.578379
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-programmed reaction of methylamine on the Ni{100} surface

Abstract: The adsorption and temperature-programmed reaction of methylamine on the Ni{100} surface is investigated. Irreversible decomposition of methylamine predominates at very low exposures in which the C–N bond scission is favored over dehydrogenation to form ammonia. At slightly higher exposures, nondissociative adsorption takes place. A new adsorption state of methylamine, in which the chemisorbed methylamine molecule is hydrogen bonded to nitrogen residues on the surface, is found which has a binding energy of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…C−N bond activation has also been observed at ∼380 K for many organonitrogen compounds on nickel surfaces, often accompanied by the desorption of the products at reaction temperature. For methylamine on the Ni(100) surface, C−N bond cleavage is observed at 380 K, yielding NH 3 and CH 4 simultaneously. , NH 3 and C 6 H 6 are also observed at 380 K during aniline 2 and cyclohexylamine 28 hydrogenolysis on the Ni(111) surface. On the basis of this evidence we propose that for aniline adsorbed on the Ni(100) surface C−N bond activation occurs near 350 K with immediate desorption of the N-containing product at this temperature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…C−N bond activation has also been observed at ∼380 K for many organonitrogen compounds on nickel surfaces, often accompanied by the desorption of the products at reaction temperature. For methylamine on the Ni(100) surface, C−N bond cleavage is observed at 380 K, yielding NH 3 and CH 4 simultaneously. , NH 3 and C 6 H 6 are also observed at 380 K during aniline 2 and cyclohexylamine 28 hydrogenolysis on the Ni(111) surface. On the basis of this evidence we propose that for aniline adsorbed on the Ni(100) surface C−N bond activation occurs near 350 K with immediate desorption of the N-containing product at this temperature.…”
Section: Discussionmentioning
confidence: 98%
“…On the Ni(100) surface, the adsorption and reaction of methylamine, [5][6][7] pyridine, 8 and aniline 5 have been previously characterized using surface analytical methods. In an EELS study by Shirley et al, 6 CH 3 NH 2 was found to adsorb associatively through the nitrogen lone pair with the C-N bond basically parallel to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…9 The selectivity of different catalysts in activating the C-H, N-H, and C-N bonds, as well as the mechanistic details, can be determined by studying methylamine decomposition. An abundance of experiments focused on the adsorption and decomposition of methylamine on Ni, 3,[9][10][11][12][13][14] Fe, 14 Cr, 3,13,14 Rh, 15 Pd, 16 Pt, [17][18][19] Mo, 20 W, 21 and Ru 22 surfaces have been performed with a variety of surface-sensitive techniques. The adsorption and decomposition of methylamine on Pt surfaces have been investigated with angle resolved ultraviolet photoemission spectroscopy (ARUPS), thermal desorption spectrometry (TDS), temperature programmed desorption (TPD), auger electron spectroscopy (AES), and electron energy loss spectroscopy (EELS).…”
Section: Introductionmentioning
confidence: 99%
“…1 Up to now, it is well-known that methylamine can be adsorbed through the nitrogen lone pair electrons on transition metal surfaces under UHV (ultrahigh vacuum) conditions, and the C-H, N-H or C-N bond can be activated at a high enough temperature. Several researchers have studied the adsorption and decomposition of methylamine on several metals, Ni, [2][3][4][5][6][7][8] Ru, 9 Pd, 10 Pt, 11,12 W, 13 Fe, 8 Cr, [6][7][8] Mo 14 and Rh. 15 The metallic Mo is very active, and it can be passivated by the carbon, nitrogen or oxygen overlayer.…”
Section: Introductionmentioning
confidence: 99%